Faktor-faktor yang mempengaruhi gejala ponteng dalam kalangan pelajar sekolah menengah Daerah Keningau, Sabah - Marcela Harry @ Saidi (2010)
This study's purpose is to identify the factors which influence the secondary students to truant from schools in Keningau, Sabah. The sample for the study includes 200 of form two and form four students. Sampling for this study is based on attendance book and Prevention of Truancy Book. Questionnaire was used as the intrument of this study. Collected data of this study is analyzed by using SPSS Version 12.0. Two statistics are used such as descriptive statistics including percentage, frequency and mean, Statistical inference t-test and Correlations Pearson. Results of the study shows that condition of school factor as the most dominant factor influencing the student to truancy from school. This research shows that there is no significant relation between factors influencing school truancy such as individual factor, condition of school, teachers, peers group, family and electronic media with family income. The finding also indicated that there were no significant difference in type of school truancy such as "heart truncy", late awakened and class truancy between male and female. The level of factors which influence secondary students in school truancy was found at moderate level